Photography Today: Between Tableau and Document - Van Gelder, Hilde (Recherches sémiotiques / Semiotic Inquiry, 2008)
This essay seeks to examine the position of photography in contemporary art or, more specifically, the way photography now hovers between tableau and the ‘document’ Three methodological levels are considered: first, a co-textual reading of select images by Jeff Wall and Allan Sekula in relation to their titles; secondly, an examination of their various treatment of pictorial elements, remnants of a long-standing artistic tradition; thirdly, at the level of the meta-text, the same images are confronted with a much broader contextual relationship. Here, the differences between two modes of working in contemporary photography — singular tableau and (pseudo-) documentary montage — become clear. A historical flashback traces this current photographic paragone back to 16th Century Southern Netherlandish art. Finally, the author raises a question pertaining to a fourth, practical level: that of the art market.